The important of effective communication - Jienbaeva Sarbinaz bisenbaevna (Periodica Journal, 2022)
Its article date about t the basic process of communication and cover some of the most difficult communication issues managers face-providing constructive and effective feedback and performance appraisal.
Keywords: effective communication; barriers; extra-linguistics elements; Non- verbal cues of elements